La mediazione civile alla luce della direttiva 2008/52/CE - trocker, nicolo; DE LUCA, ALESSANDRA (Studi e saggi, 2011)
This book brings together the proceedings of the meeting held in Florence on 21 October 2010, during which a group of Italian and foreign scholars reflected on the decisions set forth in the EC Directive 2008/52 regarding various aspects of mediation in civil and commercial matters, on the commitment that awaits the Member States called upon to implement it and on the contribution that its reception can offer to the renewal of civil justice in Europe. Even apropos the manner in which civil disputes are resolved, European integration is moving towards bringing the various national systems closer. It would, however, be mistaken to think that the differences which in the past so strongly marked the various legal systems are destined to disappear. Instead these divergences will live on in the different dimension of a shared European adventure.